Key Ingredients for the Modeling of Single‐Atom Electrocatalysts - Giovanni Di Liberto; Gianfranco Pacchioni (ChemElectroChem)
Abstract Single‐atom catalysis is gaining interest also because of its potential applications in a broad spectrum of electrochemical reactions. The reactivity of single‐atom catalysts (SACs) is typically modeled with first principles approaches taking insight from heterogenous catalysis. An increasing number of studies show that the chemistry of SACs is more complex than often assumed, and shares many aspects in common with coordination chemistry. This evidence raises challenges for computational electrocatalysis of SACs. In this perspective we highlight a few fundamental ingredients that one need to consider to provide reliable predictions on the reactivity of SACs for electrochemical applications. We discuss the role of the local coordination of the metal active phase, the need to use self‐interaction corrected functionals, in particular when systems have magnetic ground states. We highlight the formation of unconventional intermediates with respect to classical metal electrodes, the need to include the stability of SACs in electrochemical conditions and the role of solvation in the analysis of new potential catalytic systems. This brief account can be considered as a tutorial underlining the importance of treating the reactivity of SACs. In fact, neglecting some of these aspects could lead to unreliable predictions failing in the design of new electrocatalysts.